User interface (UI) design issues for multilingual users: a case study - Miraz, Mahdi H.; Excell, Peter S.; Ali, Maaruf (Universal access in the information society, 2016)
A multitude of web and desktop applications is now widely available in diverse human languages. This paper explores the design issues that are specifically relevant for multilingual users. It reports on the continued studies of Information System (IS) issues and users’ behaviour across cross-cultural and transnational boundaries. Taking the BBC website as a model that is internationally recognized, usability tests were conducted to compare different versions of the website. The dependant variables derived from the questionnaire were analysed (via descriptive statistics) to elucidate the multilingual UI design issues. Using principal component analysis, five de-correlated variables were identified, which were then used for hypotheses tests. A modified version of Herzberg’s Hygiene-motivational Theory about the Workplace was applied to assess the components used in the website. Overall, it was concluded that the English versions of the website gave superior usability results and this implies the need for deeper study of the problems in usability of the translated versions.